«Արաբական գարունը» Մաղրիբում և Թուրքիան - Ժամհարյան Արմեն (YSU Journal of International Affairs, 2014)
The article presents the relationship between Turkey and Arab Maghreb countries in the Arab Spring. Particular emphasis was placed on the Turkish model and the Arab Maghreb countries’ positions towards it. There are also introduced parties desire to imitate the Turkish mode which came to power in Maghreb. Also attention was paid to the Turkish policy towards the Maghreb countries during the Arab Spring. That policy aimed to protect and strengthen its position in the region which has a significant importance for Turkey. Submitting these and other developments, the article concludes that during the Arab Spring Turkey’s policy was successful to a large extent.